Effects of citrus essential oils on the oxidative stability of microencapsulated fish oil by spray-drying - Durmus, Mustafa; Özogul, Yesim; Ozyurt, Gulsun; Ucar, Yilmaz; Kosker, Ali Riza; Yazgan, Hatice; Ibrahim, Salam A.; Özogul, Fatih (Frontiers in Nutrition, 2023)
The effects of citrus essential oils (orange, lemon, mandarin, and grapefruit) on the oxidative stability of microencapsulated fish oil by spray-drying were evaluated. The encapsulation efficiency of microcapsules was in the range of 42.25 and 62.43%. Twelve active substances were determined as major volatile components of citrus essential oils. The highest phenolic content was obtained from grapefruit essential oil (44.32 mg GAE/g). Lower values of thiobarbituric acid reactive substances (TBARs) were obtained for microencapsulated fish oils with essential oils compared to control. At the end of storage, the highest peroxide value (PV) was observed in the control group (25.30 meq O2/kg oil) while the lowest value was in the lemon (13.40 meq O2/kg oil) and orange group (13.91 meq O2/kg oil). The results of this study showed that citrus essential oils can be used to improve the oxidative stability of fish oil microcapsules.